2010
DOI: 10.1177/0883073809341670
|View full text |Cite
|
Sign up to set email alerts
|

Brain Morphology in Autism and Fragile X Syndrome Correlates With Social IQ: First Report From the Canadian-Swiss-Egyptian Neurodevelopmental Study

Abstract: Fragile X syndrome shares most of the behavioral phenotypic similarities with autism. How are these similarities reflected in brain morphology? A total of 10 children with autism and 7 with fragile X underwent morphological (T1) 1.5-T magnetic resonance imaging (MRI). The authors found no significant difference in total brain volumes, regional volumes, gyrification index, sulcul depth, and cerebral cortical thickness. However, children with autism showed significant decrease in the medial prefrontal bilaterall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
0
9
1
Order By: Relevance
“…This is in contrast with previous studies using GI in children, adolescents or adults with ASD, which report either an increased GI (Hardan et al, 2004; Jou et al, 2010), or an absence of significant difference (Casanova et al, 2009; Kates et al, 2009; Meguid et al, 2010). Lower intellectual abilities in our patient group may explain part of the divergence with previous results, given that both studies that reported increased GI comprised participants with higher full-scale IQ scores (means: 105 ± 16 for Hardan et al (2004), 110 ± 15 for Jou et al (2010) and 113 ± 15 for Wallace et al (2013)).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This is in contrast with previous studies using GI in children, adolescents or adults with ASD, which report either an increased GI (Hardan et al, 2004; Jou et al, 2010), or an absence of significant difference (Casanova et al, 2009; Kates et al, 2009; Meguid et al, 2010). Lower intellectual abilities in our patient group may explain part of the divergence with previous results, given that both studies that reported increased GI comprised participants with higher full-scale IQ scores (means: 105 ± 16 for Hardan et al (2004), 110 ± 15 for Jou et al (2010) and 113 ± 15 for Wallace et al (2013)).…”
Section: Discussioncontrasting
confidence: 88%
“…Previous studies have noted alterations to cortical shape in autism (Levitt et al, 2003; Nordahl et al, 2007; Shokouhi et al, 2012), and some have used the Gyrification Index (GI; Hardan et al, 2004; Casanova et al, 2009; Kates et al, 2009; Jou et al, 2010; Meguid et al, 2010). Given that the cortex grows primarily through radial expansion (Rakic, 1988), the GI was specifically designed to identify early defects in cortical development.…”
Section: Introductionmentioning
confidence: 99%
“…These distinct neuroanatomical patterns are present even though multivariate pattern classification analysis using diagnostic-behavioral data could not differentiate between FXS+A and iAUT. Another recent study 25 also found neuroanatomical differences between AUT and FXS+A even though the two groups were behaviorally indistinguishable. Specifically, the group with AUT was found to have thinner cortex in the left ACC and bilateral medial PFC, as compared to the group with FXS+A.…”
Section: Commentmentioning
confidence: 80%
“…Nonetheless, underscoring the neurobiological heterogeneity of ASD, there are differences between ASD in FXS and ASD in the general population. Hoeft et al [78] and Meguid et al [79] have reported differences in the direction of morphologic abnormalities in the two types of ASD. Individuals with FXS, with or without ASD, have a larger caudate nucleus and smaller amygdala than their counterparts with idiopathic ASD [80].…”
Section: Neurobiological Correlates Of Asd In Fxs: Anomalies Of the Cmentioning
confidence: 99%